(untitled) (International Journal of Environmental Sciences, 2025)
Next-generation wireless network architectures are transforming healthcare connectivity by addressing critical limitations of traditional Wi-Fi and legacy Distributed Antenna Systems. This comprehensive article examines how Neutral Host Networks and Private Wireless Networks converge to create robust, secure, and scalable infrastructure solutions for modern healthcare facilities. The article explores five primary connectivity challenges facing healthcare organizations: coverage limitations in complex architectural environments, network congestion during peak utilization, multi-operator complexity, high implementation costs, and limited future-proofing capabilities. Through detailed examination of Multi-Operator Radio Access Network (MORAN) configurations and Private Wireless Network integration, the article demonstrates how these technologies enable superior electronic health record optimization, medical device connectivity, telemedicine services, and operational efficiency applications. The article incorporates field trial data and implementation strategies that highlight significant improvements in connection reliability, data transmission speeds, latency reduction, and patient satisfaction scores. Strategic planning requirements, including technology assessment, stakeholder engagement, and financial considerations, are analyzed alongside future scalability needs for emerging applications such as virtual reality training, artificial intelligence diagnostics, and robotic surgery systems. The findings indicate that next-generation wireless architectures provide healthcare organizations with cost-effective, secure, and adaptable connectivity solutions that support current operational requirements while enabling future digital health innovations through software-defined networking, network slicing capabilities, and edge computing integration.